Early Anglo-Saxon cemeteries - Sayer, Duncan (2020)
Early Anglo-Saxon cemeteries are well-known because of their rich grave goods, but this wealth can obscure their importance as local phenomena and the product of pluralistic multi-generational communities. This book explores over one hundred early Anglo-Saxon and some Merovingian cemeteries and aims to understand them using a multi-dimensional methodology. The performance of mortuary drama was a physical communication and so needed syntax and semantics. This local knowledge was used to negotiate the arrangement of cemetery spaces and to construct the stories that were told within them. For some families the emphasis of a mortuary ritual was on reinforcing and reproducing family narratives, but this was only one technique used to arrange cemetery space. This book offers an alternative way to explore the horizontal organisation of cemeteries from a holistic perspective. Each chapter builds on the last, using visual aesthetics, leitmotifs, spatial statistics, grave orientation, density of burial, mortuary ritual, grave goods, grave robbing, barrows, integral structures, skeletal trauma, stature, gender and age to build a detailed picture of complex mortuary spaces. This approach places community at the forefront of interpretation because people used and reused cemetery spaces and these people chose to emphasise different characteristics of the deceased because of their own attitudes, lifeways and lived experiences. This book will appeal to scholars of Anglo-Saxon studies and will also be of value to archaeologists interested in mortuary spaces, communities and social differentiation because it proposes a way to move beyond grave goods in the discussion of complex social identities.